EFFECT OF MELATONIN SUPPLEMENTATION ON PLASMA GLUCOSE AND LIVER GLYCOGEN LEVELS IN RATS SUBJECTED TO ACUTE SWIMMING EXERCISE - Kaya, Oktay; Kilic, Mehmet; Celik, Ilhami; Baltaci, Abdulkerim Kasim; Mogulkoc, Rasim (Univ Karachi, 2010)
The aim of the present study is to examine how melatonin supplementation affects plasma glucose and liver glycogen levels in rats subjected to acute swimming exercise. Spraque-Dawley species thirty adult male rats were allocated to 3 groups with equal number of animals: general control group which was not subjected to any procedure (Group 1), the group subjected to a 30-minute acute swimming exercise (Group 2), and the group subjected to a 30-minute acute swimming exercise after intraperitoneal (i.p.) melatonin supplementation (3 mg/kg/day) for 4 weeks (Group 3). Blood samples collected from the experimental animals by decapitation method were analyzed in terms of plasma glucose, and glycogen levels were determined in liver tissue samples by histological method. The highest plasma glucose levels were obtained in group 2 (p<0,05). Plasma glucose levels in groups 1 and 3 were not different. Mean liver glycogen level in group 3 was significantly higher than those in the other groups (p<0,01), while there was no significant difference between group 1 and group 2 in terms of this parameter. Results of the study demonstrate that melatonin supplementation can have a protective effect on liver glycogen reserves in rats subjected to acute swimming exercise.
Keywords: Melatonin; swimming; glucose; liver glycogen